2010
DOI: 10.1063/1.3463150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate-induced strain in the transport properties of AlGaN/GaN heterostructures

Abstract: This paper studies the effect of substrate-induced strain in the transport properties of AlGaN/GaN heterostructures grown on Si substrates by metal-organic chemical vapor deposition. Partial thinning of the original Si substrate by chemical dry etching has been used to induce controllable amounts of biaxial strain in the sample. After each etching step, Raman and Hall effect—Van Der Pauw measurements were performed as a function of remaining Si substrate thickness to study the residual biaxial strain and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 15 publications
3
42
0
1
Order By: Relevance
“…Azize and Palacios [66] reported a mobility increase by etching a Si substrate from the backside for controlling the tensile strain in AlGaN. Fehlberg et al [67] reported a high mobility of 2380 cm 2 /V s by depositing SiN films with varied deposition conditions, resulting in introduction of strain in an AlGaN layer.…”
Section: On-resistancementioning
confidence: 98%
“…Azize and Palacios [66] reported a mobility increase by etching a Si substrate from the backside for controlling the tensile strain in AlGaN. Fehlberg et al [67] reported a high mobility of 2380 cm 2 /V s by depositing SiN films with varied deposition conditions, resulting in introduction of strain in an AlGaN layer.…”
Section: On-resistancementioning
confidence: 98%
“…The stress variation is quite different from that with a Si substrate as described in Ref. [14]. Before Si substrate thinning, the original stress (strain) of the GaN layer is tensile stress, which is mainly due to the thermal expansion mismatch between the GaN layer and Si substrate [17].…”
Section: Resultsmentioning
confidence: 97%
“…When the temperature is reduced from the growth temperature to the room temperature, in-plane tensile stress (for Si substrate) and compressive stress (for sapphire substrate) in GaN layer are induced, respectively. And, when the remaining Si substrate thickness decreases, the tensile stress firstly increases (more than 350 µm Si thickness remaining) and then induces a relaxation (less than 350 µm Si thickness remaining) [14]. When the sapphire substrate thickness decreases, the compressive stress tends to increase for the remaining sapphire substrate thickness less than 170 µm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The externally induced tensile stress enhances piezoelectric polarization charge density which results in high sheet carrier density and increased mobility through techniques like substrate thinning and vacuum annealing. 15,16 But in our case, unlike the externally induced residual stress, the internal residual strain only degrades rather improve the electrical properties of the heterostructures.…”
Section: Resultsmentioning
confidence: 99%